# 3(m-3)+2(m-3)=2m-3

## Simple and best practice solution for 3(m-3)+2(m-3)=2m-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3(m-3)+2(m-3)=2m-3 equation:

Simplifying
3(m + -3) + 2(m + -3) = 2m + -3
Reorder the terms:
3(-3 + m) + 2(m + -3) = 2m + -3
(-3 * 3 + m * 3) + 2(m + -3) = 2m + -3
(-9 + 3m) + 2(m + -3) = 2m + -3
Reorder the terms:
-9 + 3m + 2(-3 + m) = 2m + -3
-9 + 3m + (-3 * 2 + m * 2) = 2m + -3
-9 + 3m + (-6 + 2m) = 2m + -3
Reorder the terms:
-9 + -6 + 3m + 2m = 2m + -3
Combine like terms: -9 + -6 = -15
-15 + 3m + 2m = 2m + -3
Combine like terms: 3m + 2m = 5m
-15 + 5m = 2m + -3
Reorder the terms:
-15 + 5m = -3 + 2m
Solving
-15 + 5m = -3 + 2m
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '-2m' to each side of the equation.
-15 + 5m + -2m = -3 + 2m + -2m
Combine like terms: 5m + -2m = 3m
-15 + 3m = -3 + 2m + -2m
Combine like terms: 2m + -2m = 0
-15 + 3m = -3 + 0
-15 + 3m = -3
Add '15' to each side of the equation.
-15 + 15 + 3m = -3 + 15
Combine like terms: -15 + 15 = 0
0 + 3m = -3 + 15
3m = -3 + 15
Combine like terms: -3 + 15 = 12
3m = 12
Divide each side by '3'.
m = 4
Simplifying
m = 4`